DEVELOPING ENGLISH SYLLABUS FOR ISLAMIC EDUCATION DEPARTMENT - Iin Baroroh Maarif (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2019)
ABSTRACT As stated in the research background, this research focuses on designing an English syllabus for students of Islamic Education Department. This study was conducted at Islamic Education Department at KH. A. Wahab Hasbullah University (UNWAHA), especially for the second semester students. The final product of this research is a set of English syllabus for Islamic Education courses in the second semester. This syllabus was specifically developed based on the students' needs for Islamic Education, as well as the needs of English lecturers at UNWAHA.The products of this research consist of an outline of the course (which involves course identity, course description, general course objectives, and meeting schedule), selection of topics and sub-topics, teaching goals (general and specific instructional goals), activities teaching and learning, time allocation, evaluation and assessment systems, and material sources and media. Keywords: English syllabus, Islamic Education department, KH. A. Wahab Hasbullah University